Estrategia comunicativa para la implementación y uso académico de un portal Web 2.0 en la carrera de Comunicación Social de la UPS-Quito - Vintimilla Álvarez, Andrés Roberto (2013)
In this project we work to develop a website version 2.0 for social communication career. With this tool we expect to improve all the communicative process between it members; students, teachers and all the people involved in the community, so they can interact and share knowledge daily. As a first step, we are going to make a diagnostic based on real information to resolve which are the communicational requires for the community.